1990
DOI: 10.1007/bf01313246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inorganic mercury on the emergence and hatching of the brine shrimpArtemia franciscana

Abstract: Abstract.We describe the effect of inorganic mercury on the emergence, hatching and growth of Artemiafraneiscana (commercially obtained). At concentrations as low as 0.01/tmol 1-1, mercury delays development of the organism, but the effect on the final number of developed brine shrimp is small. At higher concentrations, mercury has a dramatic effect, inhibiting the developmental process at the emergence and hatching stages. As recorded by light and scanning electron microscopy, organisms stalled at emergence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 43 publications
(40 reference statements)
1
30
0
Order By: Relevance
“…The EC 50 values are reported in Table 2; effects were highly reproducible across experiments (coefficient of variation, CV %, is 10.5 % and 7.0 % for DEG and SDS, respectively). Hatching has been extensively used for measuring the effects of toxicants (Go et al 1991;Migliore et al 1997;Carballo et al 2002;Sarabia et al 2003Sarabia et al , 2008Varó et al 2006) and the use of the hatching rate as endpoint criterion, seems acceptable, particularly for toxicity screening assays (Nunes et al 2006), although differences in response and sensitivity to potentially toxic compounds were found among and within Artemia strains, mainly due to differences in cyst structure and physiology (Sarabia et al 2008). The differences in experimental design can also affect results (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EC 50 values are reported in Table 2; effects were highly reproducible across experiments (coefficient of variation, CV %, is 10.5 % and 7.0 % for DEG and SDS, respectively). Hatching has been extensively used for measuring the effects of toxicants (Go et al 1991;Migliore et al 1997;Carballo et al 2002;Sarabia et al 2003Sarabia et al , 2008Varó et al 2006) and the use of the hatching rate as endpoint criterion, seems acceptable, particularly for toxicity screening assays (Nunes et al 2006), although differences in response and sensitivity to potentially toxic compounds were found among and within Artemia strains, mainly due to differences in cyst structure and physiology (Sarabia et al 2008). The differences in experimental design can also affect results (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Results of cyst toxicity tests, using different test procedures, endpoints and species, are still quite confusing, probably due to the technical discrepancies between procedures and endpoints. Go et al (1991) described sublethal effects (as morphological abnormalities) of inorganic mercury exposure on the early developmental stages of A. franciscana. Migliore et al (1997) found high toxicity to the nauplii in acute tests and both reduction in hatching rate and morphological alterations in A. franciscana cysts exposed to antibiotics.…”
mentioning
confidence: 99%
“…To quantify larval emergence and hatching ( Fig. 1) (Go et al, 1990;Rafiee et al, 1986), which served as measures of cyst development, 6 samples of 250 ml from each of three 50 ml tubes were mixed individually with 250 ml of sea water and 2 drops of Lugol's solution (Van Stappen, 1996) prior to counting with the aid of a dissecting microscope. Two drops of NaOCl [14% (technical) active chlorine] and NaOH (32% w/v) were then added to dissolve cyst shells, revealing non-hatched embryos for counting.…”
Section: Promotion Of Cyst Development By No and H 2 Omentioning
confidence: 99%
“…Emerged A. franciscana nauplii (E2) (Fig. 1a) (Go et al 1990;Liang and MacRae 1999;Jiang et al 2011), representing a life history stage actively engaged in protein synthesis and thus likely to contain Hsp40, were individually harvested from the culture with a Pasteur pipette under a dissecting microscope and homogenized to obtain RNA as described below. A. franciscana cysts were also hydrated for at least 3 h on ice in distilled H 2 O, collected by filtration, washed with cold distilled H 2 O, and incubated with vigorous shaking in seawater at 27°C.…”
Section: Methodsmentioning
confidence: 99%